Determinants of Generation Z’s Interest in Using BYOND by BSI: An Empirical Study: Faktor-Faktor yang Mempengaruhi Minat Generasi Z dalam Menggunakan BYOND by BSI: Studi Empiris - Azizi, Nadya Apriza; Umam, Khotibul; Fadllan, Fadllan (Perisai : Islamic Banking and Finance Journal, 2025)
This study aims to analyze the factors influencing Generation Z’s interest in using BYOND for BSI digital banking services, selecting ease of use, security, and service features as independent variables. The researcher used a quantitative approach, conducting a purposive survey of 120 BSI customers in Pamekasan. Data analysis used SPSS version 24 to test validity and reliability, assess classical assumptions, perform multiple linear regression, and test hypotheses. The results showed that ease of use and security had a positive, significant effect on Generation Z’s interest, while service features had no significant partial effect. The regression model explains a significant amount of variation in interest. Theoretically, this study integrates the UTAUT and TAM models in Islamic digital banking for Generation Z, highlighting service features as minimum expectations. The practical implications recommend that BSI improve its UI/UX, security, and innovative features. The limitations of this study include its local scope and low R-squared, and it offers suggestions for broader follow-up research.